Neurotrophic effects of neudesin in the central nervous system - Kimura, Ikuo; Nakayama, Yoshiaki; Zhao, Ying; Konishi, Morichika; Itoh, Nobuyuki (Frontiers in Neuroscience, 2013)
Neudesin / NENF was identified as a neurotrophic factor involved in neuronal differentiation and survival. It is abundantly expressed in the central nervous system, and its neurotrophic activity is exerted via the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways. Neudesin is also an anorexigenic factor to suppress food intake in hypotharamus. Neudesin is a member of the membrane-associated progesterone receptor (MAPR) family and shares key structural motifs with cytochrome b5-like heme/steroid-binding domain. PGRMC1, the founding member of this family, binds progesterone and the binding has been shown to induce 'rapid non-genomic effects' in biological responses that are unrelated to the nuclear progesterone receptors. Hence, neudesin may also be involved in the rapid non-genomic actions of progesterone. In this review, we summarize the identification, structure, and activity of neudesin in the central nervous system, and present an essential overview of the current understanding of their physiological roles and a prospect of elucidating non-genomic progesterone effects.